Berberine, curcumin and quercetin as potential antiparasitic agents.: Potential agents with antiparasitic capacity. - Elizondo-Luévano, Joel Horacio; Hernández-García, Magda Elizabeth; Pérez-Narváez, Oscar Alberto; Castro-Ríos, Rocío; Chávez-Montes, Abelardo (Revista de Biología Tropical, 2020)
Introduction: The indiscriminate use of antiparasitic agents has resulted in the establishment of resistance to them. Therefore, the development of new treatment alternatives is necessary. Natural products have various qualities as possible adjuvants in therapies against different etiological agents, among which its antiparasitic effects stand out. Objective: To evaluate the antiparasitic, antioxidant, cytotoxic, and cytoprotective activity of Berberine (Ber), Curcumin (Cur), and Quercetin (Qr). Methods: Analytical grade Ber, Cur, and Qr solutions were prepared, and aliquots were made at different concentrations for their evaluation against Entamoeba histolytica, Trichomonas vaginalis, and Strongyloides venezuelensis. To do this, the mean inhibitory concentration (IC50) was determined, and the antioxidant capacity (EC50) was also determined by the DPPH assay, both using the Probit statistical test. The cytotoxic and cytoprotective activity was determined by the hemolysis technique, Anova and Tukey's test were applied to determine the difference in the means in the treatments evaluated. Results: Ber, Cur, and Qr, showed activity against E. histolytica, T. vaginalis, and S. venezuelensis in-vitro. Ber presented IC50 of 1.7, 1.2, and 1.9 μM respectively, being more effective compared to Cur with IC50 of 55.3, 40.6, and 13.7 μM, or Qr with IC50 of 147.2, 93.2, and 110.9 μM, however, the best antioxidant activity (EC50 = 1.1 μg/ml), cytoprotective and less hemolytic, was presented by Qr (P < 0.001) compared to the evaluated control. Conclusions: The metabolites of natural origin berberine, curcumin, and quercetin, have activity against trophozoites of E. histolytica, T. vaginalis and larvae of S. venezuelensis in low doses comparable to the reference drugs in the case of Ber. Furthermore, these non-synthetic products of natural origin could be the subject of future research to help treat parasitosis, since in low doses, they showed antioxidant activity without showing considerable cytotoxicity in human erythrocytes.